Effect of the COVID‐19 pandemic on the mental health of carers of people with intellectual disabilities - Willner, Paul; Rose, John; Stenfert Kroese, Biza; Murphy, Glynis H; Langdon, Peter E; Clifford, Claire; Hutchings, Hayley; Watkins, Alan; Hiles, Steve; Cooper, Vivien (Journal of applied research in intellectual disabilities, 2020)
Introduction The measures implemented to manage the COVID‐19 pandemic have been shown to impair mental health. This problem is likely to be exacerbated for carers. Method Informal carers (mainly parents) of children and adults with intellectual disabilities, and a comparison group of parents of children without disabilities, completed an online questionnaire. Almost all the data were collected while strict lockdown conditions were in place. Results Relative to carers of children without intellectual disability, carers of both children and adults with intellectual disability had significantly greater levels of a wish fulfilment coping style, defeat/entrapment, anxiety, and depression. Differences were 2–3 times greater than reported in earlier pre‐pandemic studies. Positive correlations were found between objective stress scores and all mental health outcomes. Despite their greater mental health needs, carers of those with intellectual disability received less social support from a variety of sources. Conclusions The greater mental health needs of carers in the context of lesser social support raises serious concerns. We consider the policy implications of these findings.